EFEKTIFITAS PENGGUNAAN APLIKASI SIRUKIM DALAM RANGKA PENINGKATAN PENERIMAAN RETRIBUSI SEWA UNIT HUNIAN DAN UNIT USAHA DI UNIT PENGELOLA RUMAH SUSUN II PERIODE TAHUN 2023 JAKARTA UTARA - Anggita, Firly; Chaerunisyah, Ana (Jurnal Ilmu Administrasi Publik, 2025)
Payment of rental levies for residential units and business units was previously done manually. This has the potential to reduce revenue and reduce the quality of service provided to residents. The research method used is qualitative approach. The results showed that the Flat Management Unit II in improving the efficiency and effectiveness of various sectors, including the housing sector. In Indonesia, one of the technological innovations applied to support the flat management is the Sistem Informasi   Rumah   Susun   dan   Komersial   (SIRUKIM) application.